2017
DOI: 10.1002/jcph.959
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Glecaprevir and Pibrentasvir in Healthy White, Chinese, and Japanese Adult Subjects

Abstract: Glecaprevir and pibrentasvir are direct-acting antiviral agents being developed as combination therapy for the treatment of chronic hepatitis C virus infection. The aim of the present studies was to assess the effect of race and ethnicity (white, Han Chinese, Japanese) on the pharmacokinetics and safety of multiple oral doses of glecaprevir and pibrentasvir given alone and in combination. Two multiple-dose, single-center, phase 1 studies were conducted in healthy adult male and female subjects (n = 170) of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
5
20
0
Order By: Relevance
“…The proportion of pruritus in our study (7.8%) was similar to reports from Japan (6.0%‐7.3%), but tended to be higher than Western's studies (4.7%) . Although a recent pharmacokinetic study showed no differences in GLE/PIB exposure among White, Chinese, and Japanese healthy adults, the maximum plasma concentration and the area under plasma concentration‐time curve were significantly higher in Chinese and Japanese than those in Whites when GLE or PIB was administered alone . In addition to race/ethnicity, other factors, such as age, sex.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The proportion of pruritus in our study (7.8%) was similar to reports from Japan (6.0%‐7.3%), but tended to be higher than Western's studies (4.7%) . Although a recent pharmacokinetic study showed no differences in GLE/PIB exposure among White, Chinese, and Japanese healthy adults, the maximum plasma concentration and the area under plasma concentration‐time curve were significantly higher in Chinese and Japanese than those in Whites when GLE or PIB was administered alone . In addition to race/ethnicity, other factors, such as age, sex.…”
Section: Discussionsupporting
confidence: 78%
“…18,19,23,33,34 Although a recent pharmacokinetic study showed no differences in GLE/PIB exposure among White, Chinese, and Japanese healthy adults, the maximum plasma concentration and the area under plasma concentration-time curve were significantly higher in Chinese and Japanese than those in Whites when GLE or PIB was administered alone. 39…”
Section: Discussionmentioning
confidence: 99%
“…When coadministered with glecaprevir, pibrentasvir exposures are higher than for pibrentasvir alone in a mechanism attributed to inhibition of intestinal P-gp and/or BCRP by glecaprevir. These increases were similar for glecaprevir 200-400 mg doses, increasing the pibrentasvir AUC to 3.0to 3.5-fold and suggesting a saturation of this inhibition in the clinical dose range (Lin et al, 2017(Lin et al, , 2018; potent inhibition of intestinal P-gp with glecaprevir 300 mg was confirmed in the dabigatran etexilate study. Similarly, substantial OATP1B1/3 interactions for glecaprevir 300 mg were observed in subsequent studies with simvastatin and lovastatin (Mavyret, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…[13] The mean value of glecaprevir maximum plasma concentration level was reported as 1,150 to 1,390 ng/mL in normal healthy adult subjects. [14] An analysis of previous phase 2 and 3 trials showed that plasma drug concentration levels were 2.2-fold higher in patients with cirrhosis than patients without cirrhosis. [4] Even considering the higher drug concentration level in cirrhotic patients, our patient had about 13- to 16-fold higher plasma drug concentration level (18,500 ng/mL) when hyperbilirubinemia was diagnosed.…”
Section: Discussionmentioning
confidence: 99%